2016 International Congress of Entomology 2016
DOI: 10.1603/ice.2016.108782
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activities of indigenousBacillus thuringiensisisolates and nematode symbiotic bacterial toxins against the mosquito vector Culex pipiens(Diptera: Culicidae)

Abstract: Background: The incidence of mosquito-borne diseases and the resistance of mosquitoes to conventional pesticides have recently caused a panic to the authorities in the endemic countries. This study was conducted to identify native larvicidal biopesticides against Culex pipiens for utilization in the battle against mosquito-borne diseases. Methods: Larvicidal activities of new indigenous Bacillus thuringiensis isolates and crude toxin complexes (TCs) of two nematode bacterial-symbionts, Photorhabdus luminescens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(78 reference statements)
1
9
1
Order By: Relevance
“…Our data agree with the literature describing the increased efficacy of the use of entomopathogen combinations. Bt plus EPN combination was used against other insect species, such as the Coleoptera Cyclocephala hirta and Cyclocephala pasadenae 49 , the Lepidoptera Spodoptera exigua, Autographa gamma and Plutella xylostella 50 , 51 , and the Diptera Tipula paludosa 52 and Culex pipiens 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data agree with the literature describing the increased efficacy of the use of entomopathogen combinations. Bt plus EPN combination was used against other insect species, such as the Coleoptera Cyclocephala hirta and Cyclocephala pasadenae 49 , the Lepidoptera Spodoptera exigua, Autographa gamma and Plutella xylostella 50 , 51 , and the Diptera Tipula paludosa 52 and Culex pipiens 53 .…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple studies showing the histopathological effects of Cry toxins in midgut cells observed by light or transmission electron microscopy in different insect orders including lepidopteran [ 47 52 ], coleopteran [ 53 ] or dipteran larvae [ 54 57 ]. Overall, these reports show that Cry toxins induced severe vacuolization of the cytoplasm of the midgut cells, as well as loss of microvilli structure, cell lysis and columnar cells fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the known limitations of these therapeutic strategies, cancer can be cured provided that it is diagnosed at early stages. In the quest for finding an alternative cure for cancer that is more effective and specific, our research group has collected a repository of 68 Bt strains from 300 diverse environmental samples (October 2013–March 2014), isolated out of 16 sites across Saudi Arabia, and their potential larvicidal activity has previously been fully explored [12,27,38]. The present work represents the first report that examines the anticancer activity of nine non-larvicidal and non-hemolytic native Bacillus thuringiensis (Bt) isolates from different regions across Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…A total of sixty-eight B. thuringiensis (BT) isolates were obtained (October 2013–March 2014) from diverse environmental samples recovered from various locations in Saudi Arabia according to previously published protocols by our group. The full procedures of isolation, culturing and identification of Bt strains are detailed therein [12,27,38].…”
Section: Methodsmentioning
confidence: 99%